2013
DOI: 10.1590/s0100-69912013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernias in patients of 50 years and above. Pattern and outcome

Abstract: ABSTRACT ABSTRACT ABSTRACTObjective: Objective: Objective: Objective: Objective: to evaluate a one year experience with inguinal hernia repair, in patients of > 50years, with respect to the type of inguinal hernia, type of surgery, postoperative complications and recurrence. Methods:Methods: Methods: Methods: Methods: a prospective descriptive study of patients (n=57) > 50 years operated for inguinal hernia during a one year period. Tension-free meshplasty and herniorrhaphy, using 3"x6" polypropylene mesh and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
3
5
0
22
Order By: Relevance
“…In case of emergency surgery, most patients hospitalized for one to three days. In this study, male patients out-numbered female patients, the reason for the male predominance may be the inherent weakness of the abdominal wall where the spermatic cord passes through the inguinal canal, which consistent with the results of other studies [4][5][6][7]. We observed that 52 (20.8%) patients had a family history of inguinal hernia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In case of emergency surgery, most patients hospitalized for one to three days. In this study, male patients out-numbered female patients, the reason for the male predominance may be the inherent weakness of the abdominal wall where the spermatic cord passes through the inguinal canal, which consistent with the results of other studies [4][5][6][7]. We observed that 52 (20.8%) patients had a family history of inguinal hernia.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 60% of patient had right-sided hernia, fewer had left-side hernia, while bilateral hernia was the least common. Other studies have also reported similar results [5,10,11,14]. The right side is believed to be predominantly affected due to the delayed descent of the right testis and subsequence failure of closure of processus vaginalis [10,[15][16][17].…”
Section: Discussionsupporting
confidence: 53%
“…Direct hernia was seen in 30 patients (52.63%) and indirect hernia was seen in 27 (47.36%) patients. 12 Direct inguinal hernia is more common in adult population as in present study.…”
Section: Discussionsupporting
confidence: 49%
“…A dor crônica após HPI está relacionada com a lesão tecidual e neuronal locais durante a cirurgia, assim como o processo cicatricial produzido pela sutura ou pela própria tela [12][13][14] . Esta complicação apresenta taxa de incidência que varia de 11% para 60,8% [15][16][17] , impactando na qualidade de vida do paciente. Dentre os fatores de risco que desenvolvem dor crônica, destacam-se fatores psicossociais, idade jovem e o elevado nível de dor antes da cirurgia [18][19][20][21] .…”
Section: Introductionunclassified